Bone mineral density and content in adolescent girls. DOI: 10.5007/1980-0037.2011v13n5p354 - Nanci Maria de França; Rinaldo Wellerson Pereira; Romulo Maia Carlos Fonseca (Universidade Federal de Santa Catarina, 2011)
The aim of the present study was to characterize bone mineral density (BMD) and content (BMC) in Brazilian adolescent girls according to age and pubertal stage. A total of 329 girls ranging in age from 10 to 20 years participated in this study. Body weight, height, body mass index, pubertal stage, race, daily calcium intake, and time spent per week performing moderate to vigorous-intensity physical activity (MVPA) were evaluated. Lumbar spine and femoral neck BMD and BMC were assessed by dual-energy x-ray absorptiometry. One-way ANOVA with Tukey post-hoc test was used to identify differences in bone mass between ages and pubertal stages (p≤0.05). The daily calcium intake reported by the adolescents was inadequate, corresponding to only 26-47% of the recommended allowance (1,300 mg/day). On the other hand, weekly MVPA was higher than that recommended for adolescents. Significant differences in BMD and BMC were observed for girls aged 10-14 years. In addition, lumbar spine and femoral neck BMD was 58 and 31% higher in postpubertal girls, respectively, when compared to prepubertal adolescents.